2015
DOI: 10.1007/s00214-015-1691-x
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of nitric oxide with water and imidazole

Abstract: NO-Imi-H 2 O complexes can be used as a model to investigate the interactions of histidine with nitric oxide and water in biological systems like myoglobin. We discuss here the water-imidazole, water-nitric oxide dimers and the trimolecular complexes of nitric oxide with water and imidazole from the donor-acceptor point of view using the Natural Bond Orbitals (NBO) and Energy Decomposition Analysis (EDA) schemes. The comparison between trimolecular and bimolecular complexes shows that in general, the stabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Finally, several additional theoretical studies have attempted to develop insights into the physical origin of the intermolecular interactions in the NO + H 2 O complex, as well as map out the D 0 and D 1 PESs. 29–31 Outside of the CASSCF calculations reported by Umemoto and co-workers, the photochemistry of NO (A 2 Σ + ) + H 2 O has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several additional theoretical studies have attempted to develop insights into the physical origin of the intermolecular interactions in the NO + H 2 O complex, as well as map out the D 0 and D 1 PESs. 29–31 Outside of the CASSCF calculations reported by Umemoto and co-workers, the photochemistry of NO (A 2 Σ + ) + H 2 O has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…15 Several theoretical analyses, like the quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO), were used to characterize and quantify the nature of interactions in the NO(H 2 O) complex. 11,16,17 Despite the importance of NO and water interactions in several research areas, the microhydration of NO has not been explored well at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Atomistic-level insights into hydrated NO and identification of the nature of noncovalent interactions among them have received immense attention in recent years. Several research groups confirmed the hydrogen bond (HB) interaction between neutral NO and water with the help of infrared spectrum, mass spectrometry, and laser techniques. The potential energy surface of NO­(H 2 O) complexes at the ab initio level was initially reported by Myszkiewicz and Sadlej . Several theoretical analyses, like the quantum theory of atoms in molecules (QTAIM) and natural bond orbital (NBO), were used to characterize and quantify the nature of interactions in the NO­(H 2 O) complex. ,, Despite the importance of NO and water interactions in several research areas, the microhydration of NO has not been explored well at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation